2021
DOI: 10.1186/s12939-021-01544-w
|View full text |Cite
|
Sign up to set email alerts
|

The evolution trend of availability of China’s community-based care services and its impact on the cognitive function of elderly people: 2008-2018

Abstract: Background To address the challenge of the aging population, community-based care services (CBCS) have been developed rapidly in China as a new way of satisfying the needs of elderly people. Few studies have described the evolution trend of availability of CBCS in rural and urban areas and evaluated their effectiveness. This study aims to show the availability of China’s CBCS and further analyze the effect of the CBCS on the cognitive function of elderly people. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 58 publications
2
29
0
Order By: Relevance
“…The results of regression analysis also showed that age had significant negative impact on the cognitive function ( p < 0.001), ADL ( p < 0.001), and symptoms of depression ( p < 0.001), which suggest that older adults tend to have worse cognitive function, ADL, and symptoms of depression. This finding was consistent with several studies ( 61 63 ). As we all know, age plays a fundamental role in the health of older adults.…”
Section: Discussionsupporting
confidence: 94%
“…The results of regression analysis also showed that age had significant negative impact on the cognitive function ( p < 0.001), ADL ( p < 0.001), and symptoms of depression ( p < 0.001), which suggest that older adults tend to have worse cognitive function, ADL, and symptoms of depression. This finding was consistent with several studies ( 61 63 ). As we all know, age plays a fundamental role in the health of older adults.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the community environment also affects their cognitive function ( Xiang et al, 2018 ). There is a positive correlation between community infrastructure and cognitive function, especially health and entertainment facilities ( Yue et al, 2021 ). Emotional community support is mainly transferred through the processing of family relations and neighborhood relations, as well as the expansion of social networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although life expectancy continued to increase, it was necessary to consider adverse outcomes in advance given the increasing likelihood that cognitive ability will decline with age. A previous study showed that deterioration of cognitive ability could lead to physical dysfunction and certain chronic diseases, and severe deterioration of cognitive ability was highly associated with mortality ( Yue et al, 2021 ). Furthermore, the decline of subjective (slight) cognitive ability could be regarded as a precursor of dementia, which seriously impaired the health-related quality of life of older adults ( Pusswald et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, consequences of cognitive decline in older adults not only damaged physical health, but also significantly increased the probability of Alzheimer’s disease ( Prince et al, 2013 ). Last but not least, deterioration of cognitive ability could lead to physical dysfunction and certain chronic diseases, and severe deterioration of cognitive ability was highly associated with mortality ( Yue et al, 2021 ). Therefore, it was important and urgent to study the changing trajectory of cognitive ability of older adults.…”
Section: Introductionmentioning
confidence: 99%